Active nonlinear buckling control of optimally designed laminated plates using SMA and PZT actuators. (December 2022) - Luo, Quantian; Tong, Liyong; Bambach, Mike; Rasmussen, Kim J.R.; Khezri, Mani
Abstract: This study presents an experimental investigation into active nonlinear buckling control of optimally designed laminated plates via a new control method using shape memory alloy (SMA) and piezoelectric (PZT) actuators. In this control method, the SMA actuators are used to control the magnitude of plate buckling deformation whereas the PZT actuators are mainly used to control the direction of plate buckling deformation by inducing initial bending in a desired direction. New problem formulation and solution algorithm are presented for the concurrent design optimization of PZT actuators and their host structure for maximizing targeted plate buckling deformation. Specimens are prepared using the 3D printing technique based on one selected optimum design of the PZT laminated plate. An active buckling control experiment is conducted to demonstrate the proposed control of both the direction and magnitude of plate buckling deformation via PZT and SMA actuators. A comparison between the present experimental and numerical results indicates a reasonable correlation in the buckling deformations at the selected observation points. Highlights: A hybrid actuation method to control plate buckling direction and magnitude. A simple formulation for maximizing plate nonlinear displacement and airflow. An algorithm for optimizing both PZT and host materials of a layered plate. An experimental verification of the hybrid actuation method and algorithm.